2022
DOI: 10.3389/fmed.2022.836873
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Use of Amniotic Membrane for Tectonic Repair of Peripheral Ulcerative Keratitis With Corneal Perforation

Abstract: PurposeTo provide a perspective and surgical video demonstration of peripheral corneal ulceration and perforation managed with multilayered amniotic membrane transplantation.Case ReportsCase 1 describes a 48-year-old female with progressive redness and pain, and an inferonasal corneal thinning and perforation in the left eye from peripheral ulcerative keratitis. She underwent conjunctival recession with amniotic membrane inlay and onlay (Sandwich technique) transplantation. The amniotic membrane integrated wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Hoffman et al [14]. reported a primary success rate of 11/12(92%) as compared to 11/15(73.33%) in the present study Similar results were shown by Eslami M et al [33]. who reported successful use of multilayered amniotic membrane transplantation for the treatment of corneal ulceration and perforation.…”
Section: Recurrencesupporting
confidence: 89%
“…Hoffman et al [14]. reported a primary success rate of 11/12(92%) as compared to 11/15(73.33%) in the present study Similar results were shown by Eslami M et al [33]. who reported successful use of multilayered amniotic membrane transplantation for the treatment of corneal ulceration and perforation.…”
Section: Recurrencesupporting
confidence: 89%
“…In the second case, Snellen's visual acuity at the 1-month and 4month postoperative visit was 6/90 in RE (with cataract) and 6/9 in LE with normal intraocular pressures and a quiet ocular surface. 12 The relative ease of availability of AM compared to donor cornea makes this an attractive choice for the management of corneal defects. it may be an appropriate temporizing measure to allow for an uninflamed and quiet eye prior to donor corneal graft transplantation, thereby increasing success for visual rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…it may be an appropriate temporizing measure to allow for an uninflamed and quiet eye prior to donor corneal graft transplantation, thereby increasing success for visual rehabilitation. 12 There is no absolute perforation size cut-off for the use of AM transplantation. It may be difficult to pack and close large perforation defects and restore the globe's integrity.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study discussed the role of combined UCP grafting and HAM transplantation in managing corneal perforation or descemetocele in eyes with active keratitis [4]. However, most prior research has emphasized the role of HAM transplantation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…HAM acts as a graft or temporary patch by promoting corneal epithelialization and preventing stromal inflammation, angiogenesis, and scarring [ 8 ]. Typically, multiple layers of HAM are used to treat deep corneal ulcers or perforations [ 9 ]. However, because of its weak tectonic support, HAM carries the risk of early dissolution or dislocation before the healing of corneal perforation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%